The Effect of Trigonella foemun-gracum Extract on the Fungi that Isolated from Cleaning Powder (Soap) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study  included the isolation and diagnosis of the fungi from the cleaning   powder in the soap(Laundries' staff, Laundries   of student). The study appeared many  of the different kinds of fungi:( Absidia sp,Candidia sp, Aspergillus  sp,Penicillum  sp).                           The  rate of appearance of the type of the fungi  in  Laundries '  staff  is the higher than the  laundries'  of the students.The rate of appearance of the fungi   Absidia is recoded 36.8% and Candidia ,Aspergillus niger  is recoded 21.05% and Aspergillus flavus recoded 5.2 %  , Penicillum sp recoded  15.7% while  in the laundries of students the fungi Aspergillus  niger is recorded 15.7% and the fungi  Absidia ,Candidia, Apergillus terrus is recoded 20%  ,  Penicillum sp ,Alternaria sp is recoded  10%.The study  showed  the influence  of the heating  water  extract  hot watering  extract  the race track in the concentration which is used( 10,20,30, 40) mg /ml on some of fungi. The rate of reduction is appeared 100% of the  fungi Absidia in the concentration (30,40) mg/ml and  the  range of the diameter colony of the yeast Candidia  albicanis in the concentration 30 mg/ml the (1)sanatamtar. While the fungi Aspergillus  niger in the concentration (10,20)mg/ml is not given any resistance toward the extract.